What do we know about the effects of pornography after fifty years of academic research? - McKee, Alan; Litsou, Kateriana; Byron, Paul; Ingham, Roger (Routledge, Taylor & Francis Group, 2022)
"This book presents an innovative cross-disciplinary report on research across the humanities and social sciences about the relationship between pornography and its consumers. For policy makers and the wider public it can be difficult to obtain a clear understanding of the current state of knowledge on pornography and its relationships with audiences, due to the often-contradictory nature of research spanning the various and politically diverse academic disciplines. The cross-disciplinary expertise of the author team has engaged in an extensive examination of the findings of academic research in the area in order to explain, in a clear and accessible style, the most important conclusions about the relationship of pornography to Healthy Sexual Development. This short and accessible overview is suitable for students and scholars in Psychology, Sexual Health, Film Studies, Sex Education, Queer Theory, Gender Studies, Sexuality Studies, Sociology, Media Studies, and Cultural Studies"--
"Routledge Focus"--from cover
Keywords: Geschichte 1970-; Interdisziplinarität; Rezeption; Pornografie; Forschung; Sexualverhalten; Pornography; Sex; Erotica; Sexual Behavior; Pornographie; Sexualité; sexuality; Aufsatzsammlung